S106 Tiotropium respimat® reduces episodes of asthma worsening in primotina-asthma®, irrespective of baseline characteristics or season. (December 2018) - FitzGerald, JM; Buhl, R; Casale, TB; Engel, M; Sigmund, R; Halpin, DM
Abstract : Introduction: We performed a comprehensive assessment of the effect of tiotropium Respimat ® add-on therapy on episodes of asthma worsening in adult patients with symptomatic asthma despite inhaled corticosteroid (ICS)/long-acting beta2-agonist (LABA) treatment. Methods: The PrimoTinA-asthma ® studies (NCT00772538 /NCT00776984) were two replicate 48 week, Phase III trials, which, when pooled, were powered to investigate the effect of tiotropium Respimat ® 5 µg (as two puffs once daily) or placebo on episodes of asthma worsening and exacerbations when added onto ICS ≥800 µg budesonide equivalent/day+LABA± additional controller medication. Endpoints included time to first episode of asthma worsening during the 48 week treatment period – defined as either a progressive increase in symptoms (as compared with usual day-to-day asthma symptoms) or a decline of ≥30% in morning peak expiratory flow for ≥2 consecutive days – and number of episodes of asthma worsening per patient. Time to first asthma worsening was also analysed by baseline patient characteristics, and number of episodes was analysed by month in order to determine any seasonality effect. Results: In pooled data from the two studies (n=912), time to first asthma worsening was longer in the tiotropium group compared with placebo, with a 31% risk reduction (hazard ratio 0.69; 95% confidence interval [CI] 0.58, 0.82; p<0.0001). The total number of all episodes of asthma worsening was lower in patients receiving tiotropium versus placebo (rate ratio 0.76; 95% CI 0.63, 0.91; p=0.0031). Improvements in time to first episode of asthma worsening following tiotropium treatment compared with placebo were consistent across multiple subgroups, defined by baseline characteristics. When the number of episodes of asthma worsening were plotted by month, tiotropium add-on treatment was shown to reduce episodes compared with placebo across all seasons, particularly during the autumn peak (figure 1). Conclusion: Tiotropium Respimat ® add-on therapy reduced the rate of episodes of asthma worsening in adults with symptomatic severe asthma, irrespective of several baseline characteristics, allergic characteristics, and across seasons, including the autumn peak. This comprehensive assessment of the effect of tiotropium on asthma worsening in PrimoTinA-asthma ® broadens the evidence supporting the use of tiotropium as add-on therapy in patients with symptomatic asthma despite ICS/LABA therapy. Please refer to page A265 for declarations of interest related to this abstract.